Clostridium difficile infection increases acute and chronic morbidity and mortality. (9th November 2018) - Olsen, Margaret A.; Stwalley, Dustin; Demont, Clarisse; Dubberke, Erik R.
Abstract: Objective: In this study, we aimed to quantify short- and long-term outcomes of Clostridium difficile infection (CDI) in the elderly, including all-cause mortality, transfer to a facility, and hospitalizations. Design: Retrospective study using 2011 Medicare claims data, including all elderly persons coded for CDI and a sample of uninfected persons. Analysis of propensity score-matched pairs and the entire population stratified by the propensity score was used to determine the risk of all-cause mortality, new transfer to a long-term care facility (LTCF), and short-term skilled nursing facility (SNF), and subsequent hospitalizations within 30, 90, and 365 days. Results: The claims records of 174, 903 patients coded for CDI were compared with those of 1, 318, 538 control patients. CDI was associated with increased risk of death (odds ratio [OR], 1.77; 95% confidence interval [CI], 1.74–1.81; attributable mortality, 10.9%), new LTCF transfer (OR, 1.74; 95% CI, 1.67–1.82), and new SNF transfer (OR, 2.52; 95% CI, 2.46–2.58) within 30 days in matched-pairs analyses. In a stratified analysis, CDI was associated with greatest risk of 30-day all-cause mortality in persons with lowest baseline probability of CDI (hazard ratio [HR], 3.04; 95% CI, 2.83–3.26); the risk progressively decreased as the baseline probability of CDI increased. CDI was also associated with increased risk of subsequent 30-day, 90-day, and 1-year hospitalization. Conclusions: CDI was associated with increased risk of short- and long-term adverse outcomes, including transfer to short- and long-term care facilities, hospitalization, and all-cause mortality. The magnitude of mortality risk varied depending on baseline probability of CDI, suggesting that even lower-risk patients may benefit from interventions to prevent CDI.